Merawat Bumi Ciptaan Allah: Tanggung Jawab Ekoteologis GMIT Jemaat Lopo Maus Klasis Kupang Barat dalam Memanfaatkan Lahan Tidur - Hanokh A. Tefnay; Ezra Tari; Lanny Isabela Dwisyahri Koroh (Sekolah Tinggi Alkitab Jember, 2022)
This paper will describe the practice of ecological responsibility that has been implemented in the Lopo Maus Congregation. The author began to stir the congregation when he saw land that was not being used. Even though the people around the Lopo Maus congregation have a large land area, striving for this land is to build an economy that is still below the poverty line. The challenge for land management in Kupang is that there is very little water. This writing aims to make the community make the best use of the land. This effort is made so that people love the environment more. The method that I use is qualitative, an objective approach that is carried out in the field. The results of the study found that first, land management requires persistence and patience. Second, good teamwork. Third, creating jobs. Fourth, environmental management as a concrete form of worship. Fifth, it can improve people's lives.